STUDENTS’ DIGITAL VOCABULARY LEARNING: EXPERIENCES, BARRIERS, AND ADAPTIVE STRATEGIES EXPLORATION - Muryani, Rera Nadian; Yunus, Muhammad (University of Kuningan, 2024)
This study aims to explore the experiences of students as they navigate individualized obstacles in the learning of digital vocabulary. The research employs a research methodology of a qualitative research, specifically employing a design centered around narrative inquiry, with the purpose of examining the subject matter. Specifically, the research examines the barriers faced by students in their pursuit of proficient acquisition of vocabulary through digital means, with a focus on the barriers that hinder optimal comprehension and retention. The findings of the research illuminate that students encounter both internal and external obstacles when learning vocabulary through the use of digital tools, as revealed by research. In addition, the findings reveal that students strategically combine different resources in order to enhance their vocabulary acquisition experience. This research offers practical insights to refine and enhance methods of vocabulary instruction in the digital age. A more efficient, inclusive, and captivating digital vocabulary learning environment for students can be created by educators, curriculum designers, and technology makers with an understanding of these issues and adaptable solutions. It is crucial for educators and developers to prioritize the inclusion of interactive elements in their digital vocabulary tools to address the identified need for heightened engagement and cognitive involvement in the vocabulary acquisition process.